Effect of differently processed African yam beans (sphenostylis stenocarpa harms) on performance of African catfish (Clarias gariepinus) juveniles (2011)
A 12-week feeding trial was conducted in 27-cm3 circular plastic tanks (50 × 34 cm) to assess the performance of juvenile African catfish (Clarias gariepinus) fed diets containing African yam bean meals (Sphenostylis stenocarpa) processed by different techniques. Five 35% crude protein diets were formulated containing no yam bean meal (control) or 34% fishmeal and 66% yam bean meal. The yam bean meals were processed in four manners: (a) ‘cooked’, sun-dried, and ground, (b) ‘toasted’, cooled, and ground, (c) ‘soaked’, cooked, sun-dried, and ground, (d) soaked, ‘dehulled’, cooked, and ground. Each treatment was replicated thrice, each replicate contained 15 fish (3.97±0.03 g, 8.70±0.97 cm). Fish were fed thrice daily at 5% of their body weight per day. Fish fed the control diet perfomed better (p<0.05) than those fed the diets containing yam bean meal. Among the diets containing yam bean meal, the ‘soaking’ treatment produced the best results. In all diets, the packed cell volume, hemoglobin concentration, red blood cell count, white blood cell count, erythrocyte sedimentation rate, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, lymphocytes, and neutrophils were within the ranges for healthy fish. Therefore, since the differences in fish performance between the control and the ‘soaked’ diet were less than with other yam bean diets, and because this diet was more cost-efficient than the control fishmeal diet, we conclude that soaked, cooked, and ground African yam beans can partially replace fishmeal in diets for African catfish without compromising growth or nutrient utilization